Eksplorasi dan Digitalisasi Manuskrip Keagamaan: Pengalaman di Minangkabau - Ridwan Bustamam (Jurnal Lektur Keagamaan, 2017)
Islamic Manuscript of Nusantara has long been the object of research. Center for Research and Development of Religious Literature and Heritage Office for Research and Development and Training began to seriously conserve the manuscript systematically since 2008 until now, among others through the digitalization of religious classical manuscripts. Until 2016, about 2,203 titles of religious manuscripts were successfully digitized from various parts of Indonesia, including the religious manuscripts of West Sumatra. Digitalization activities in this area are not as easy as planned, many obstacles to be faced by the digital team, technical issues and obstacles that arise from the owner of the script itself. The implementation strategy of digitizing manuscript used such as involving manuscripts from MANASSA, SULUAH Padang, IAIN Imam Bonjol Padang, and Andalas Padang University. In fact, there are still many religious manuscripts in West Sumatera that have not been photographed until 2016. Due to limited quotas, the manuscripts that are digitized are only 45 manuscripts, coming from three regions: 1) Pauh Kambar Hilir, Nan Sabaris, Padang Pariaman; 2) Batu Baraia, Saturday Feed, Luhak, Fifty Koto; 3) Kasiak, Koto Sani, Sumani, Solok. This community-owned manuscript contains among others tauhid, tafseer, fiqh, mujarabat, falakiyah, nahwu-naraf knowledge, and tasawuf. One of the most important recommendations of the digitalization team is: "intensive coordination and collaboration is needed in order to save the manuscript, because if done separately, the conservation effort of the manuscript will not run optimally.Keywords: exploration, digitizing, religious manuscripts, West Sumatra, Minangkabau  Naskah klasik (manuskrip) keislaman Nusantara sudah lama menyita perhatian para peneliti dari dalam maupun luar negeri. Puslitbang Lektur dan Khazanah Keagamaan Badan Litbang dan Diklat Kementerian Agama mulai serius mengkonservasi naskah kuno secara sistematis sejak tahun 2008 sampai sekarang, antara lain melalui digitalisasi naskah klasik keagamaan. Hingga tahun 2016, sekitar 2.203 judul naskah keagamaan telah berhasil didigital dari berbagai wilayah di Indonesia, termasuk di dalamnya manuskrip keagamaan dari Sumatera Barat. Kegiatan digitalisasi di daerah ini pun tidak semudah yang direncanakan, banyak kendala yang harus dihadapi oleh tim digital, baik kendala yang bersifat teknis maupun kendala yang berasal dari pemilik naskah itu sendiri. Strategi digitalisasi naskah yang digunakan misalnya melibatkan para pegiat naskah dari MANASSA, SULUAH Padang, IAIN Imam Bonjol Padang, dan Universitas Andalas Padang. Sesungguhnya masih banyak manuskrip keagamaan di Sumbar yang belum difoto tahun 2016. Karena kuota yang terbatas, maka manuskrip keagamaan yang didigital hanya berjumlah 45 naskah, yaitu dari tiga daerah: 1) Pauh Kambar Hilir, Nan Sabaris, Padang Pariaman; 2) Batu Baraia, Pakan Sabtu, Luhak, Lima Puluh Koto; 3) Kasiak, Koto Sani, Sumani, Solok. Naskah milik masyarakat ini berisi antara lain tauhid, tafsir, fikih, mujarabat, falakiyah, ilmu nahwu-saraf, dan tasawuf. Tim digitalisasi manuskrip keagamaan Sumbar akhirnya merumuskan rekomandasi, yang terpenting adalah: “perlu koordinasi dan kolaborasi secara intensif dalam rangka penyelamatan manuskrip, sebab jika dilakukan secara terpisah-pisah, maka upaya konservasi manuskrip tidak akan berjalan secara optimal.Kata kunci: eksplorasi, digitalisasi, manuskrip keagamaan, Sumatera Barat, Minangkabau